Ukuran Linier Tubuh Babi Lokal Timor Jantan Yang Dipelihara Secara Ekstensif - Redempta Wea; Theresia Indah Koni (Partner, 2012)
Linear Body Size Of East Local Male Pig On Extensively Cultivated. A study has been conducted with the aim of identifying the linier body size studies timor local male pigs reared extensively.Â  This research has been started since March to December 2011. The tools used are tape meter, meter sticks, and scales. Materials used are locally timor male pigs raised extensively with a lifespan of 2 to 3.9 months, from 4 to 5.9 months, and 6 to 7.9 months and the water. Research variables are body temperature and linear body size. The results showed that body temperature 38-390C on average 38.830C and Linear body size on average: Age range 2 to 3.9 months; body length 33.25 cm shoulder height 29.50 cm 36.83 cm chest circumference; length fur 2.82 cm diameter below the head / snout 3.42 cm and the head of the top 7,35 cm neck diameter 7.83 cm; front leg length 24.33 cm and 27.17 cm rear leg.Age range 4 to 5.9 months; body length 38.08 cm shoulder height 34.67 cm chest circumference 46 cm; length fur 3.82; diameter below the head / snout 5.27 cm and 17.40 cm above the head ; neck diameter 18.02 cm 29.90 cm long front legs and hind feet 35.42 inches. Age range 6 to 7.9 months; body length 46.17 cm shoulder height 50.83 cm 65.50 cm chest circumference; long hair 5.3 cm diameter below the head / snout 9.22 cm and the head of 23 cm neck diameter 26.07 cm 36.50 cm long front legs and hind feet 41.58 inches; and the appearance of coarse hairs, especially along the back.Key words :Â  Linear Body Size, Timor Local Male Pig, Extensively